2016
DOI: 10.1016/j.anr.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence and Job Outcomes of Newly Licensed Nurses

Abstract: Workplace violence is experienced by a high percentage of newly licensed nurses, and is associated with their job outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
1
15

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(125 citation statements)
references
References 28 publications
12
97
1
15
Order By: Relevance
“…We did confirm that non-physical violence was more prevalent than physical violence, which was consistent with previous studies (Lo, Chappell, Kwok, & Wu, 2012;Parent-Thirion et al, 2016). Yet, the prevalence is still much higher than that found in health care workers and general workers (Chang & Cho, 2016;Cheng & Cheng, 2017;Guay, Goncalves, & Jarvis, 2014). A study in Chinese hospital-employed nurses also found a high prevalence (72%) of workplace violence in 1 year (Jiao et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We did confirm that non-physical violence was more prevalent than physical violence, which was consistent with previous studies (Lo, Chappell, Kwok, & Wu, 2012;Parent-Thirion et al, 2016). Yet, the prevalence is still much higher than that found in health care workers and general workers (Chang & Cho, 2016;Cheng & Cheng, 2017;Guay, Goncalves, & Jarvis, 2014). A study in Chinese hospital-employed nurses also found a high prevalence (72%) of workplace violence in 1 year (Jiao et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…A study in Chinese hospital‐employed nurses also found a high prevalence (72%) of workplace violence in 1 year (Jiao et al., ). Among hospital‐employed nurses, work unit, public or private‐owned hospital and age (tenure) were associated with workplace violence (Chang & Cho, ). Hence, sample difference may explain the wide variation of 1‐year prevalence of workplace violence found among studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the literature, as indicated in research by Lee & Ji [28], having good relationships with members of the team reduces levels of exhaustion. Conversely, negative relationships and conflict are associated with higher levels of burnout [43]. Similarly, the lowest levels of burnout being in nurses who spent more of their work day with colleagues and patients may be due to less time pressure.…”
Section: Discussionmentioning
confidence: 96%
“…Such emotionally charged experiences are often associated with nurses' lower wellbeing and higher levels of burnout and turnover intentions (Karimi, Leggat, Donohue, Farrell, & Couper, 2014;McDonald, Jackson, Wilkes, & Vickers, 2016). Additionally, negative experiences with patients behaviour, such as verbal aggression, violence and sexual harassment, are associated with novice nurses' job satisfaction, burnout and intention to leave (Chang & Cho, 2016;Roche, Diers, Duffield, & Catling-Paull, 2010;Viotti, Gilardi, Guglielmetti, & Converso, 2015).…”
Section: Stressors Related To Patientsmentioning
confidence: 99%